Prevalence of Diterpenes in Essential Oil of Euphorbia mauritanica L.: Detailed Chemical Profile, Antioxidant, Cytotoxic and Phytotoxic Activities. Issue 7 (7th June 2021) - Essa, Ahmed F.; El‐Hawary, Seham S.; Abd‐El Gawad, Ahmed M.; Kubacy, Tahia M.; A. M. El‐Khrisy, Ezz El‐Din; Elshamy, Abdelsamed I.; Younis, Inas Y.
Abstract: Plants belonging to Euphorbia L. genus are considered very interesting from a medicinal point of view due to their diverse metabolites and bioactivities. The essential oil (EO) of Euphorbia mauritanica L. is not studied up to date. Therefore, the present study aimed to explore the chemical profile of this EO and evaluate its antioxidant, cytotoxic, and allelopathic potentialities. The EO was extracted from the whole plant via hydrodistillation and then, analyzed by gas chromatography/mass spectrometry (GC/MS). The correlation of E. mauritanica with the other Euphorbia plants was established using chemometric analysis. The antioxidant activity was determined based on scavenging of the free radical, 1, 1‐diphenyl‐2‐picrylhydrazyl (DPPH) and 2, 2′‐azinobis(3‐ethylbenzothiazoline‐6‐sulfonic acid) (ABTS). The anti‐proliferation of the EO on the Hep G2 and MCF‐7 cells was evaluated. Finally the allelopathic activity of the EO was assessed against the two noxious weeds, Dactyloctenium aegyptium and Urospermum picroides . Forty‐one compounds were identified using GC/MS analysis, with an abundance of terpenoids (91.54 %) that were categorized into mono‐ (30.75 %), sesqui‐ (15.23 %), and diterpenes (45.56 %). Interestingly, the results revealed the preponderance of diterpenoid constituents although they are rarely found in the EOs of the plant kingdom. The major compounds were (3 E )‐cembrene A (18.66 %), verticiol (17.05 %), limonene (7.91 %), eucalyptol (7.26 %), α‐pinene (5.61 %), neo‐cembrene A (3.52 %), kaur‐16‐ene (3.24 %), and cembrene (3.09 %). The EO showed moderate antioxidant activity where it attained IC50 values of 83.34 and 64.21 μg mL −1 for DPPH and ABTS compared to 23.01 and 19.23 μg mL −1 for ascorbic acid as standard, respectively. The EO exhibited very weak cytotoxic effect on MCF‐7 and Hep G2 cells. The EO showed significant allelopathic activities against the weeds D. aegyptium and U. picroides in a concentration‐dependent manner. EO was found more effective against U. picroides than D. aegyptium with IC50 values of 0.79, 0.45, and 0.67 mg mL −1 and 1.17, 0.55, and 1.08 mg mL −1 for germination, root, and shoot growth, respectively. Due to the high content of diterpenes in E. mauritanica, further study is recommended for more characterization of pure forms of the identified diterpenes as well as evaluating their bioactivity either solely or synergistically. Abstract :